Class-Discussion as an Effective Form of Study Internal Medicine - Yatsyshyn, Roman; Cherniuk, Nataliia; Gerych, Petro; Drogomeretska, Oksana; Kuryliv, Halyna (Journal of Vasyl Stefanyk Precarpathian National University, 2021)
In order to improve the quality of studying of fourth-year students of the Medical Faculty and the Foreign Citizens Training Faculty, as well as to intensify the educational process at the Department of Internal Medicine, Clinical Immunology and Allergology of Ivano-Frankivsk National Medical University a modern class-discussion was introduced. For a successful discussion a clear organization of the class has been proposed. It implies careful planning, clear implementation of the rules of the discussion by all its participants, compliance with certain regulations. The class-discussion consists of the following main stages: entrance testing by QR-code for quick assessment of the level of knowledge and obtaining rating indicators from individual sections of the discipline; short summary multimedia presentation on modern methods of diagnosis and principles of treatment of the diseases of a certain profile; application of the elements of role-play (simulation): students’ role-playing of the patient, family doctor, laboratory doctor, doctor of functional diagnostics, doctor-specialist, the head of the hospital with the subsequent modeling of various clinical situations. Thus, the class-discussion in the proposed form with elements of interactive learning is a versatile type of practical lesson, which increases students' ability to think analytically; develops research, communication, heuristic, and leadership skills as well as the ability to make informed decisions about the patient's further clinical route. It contributes to the consolidation and integrated application of the knowledge obtained during the study of the discipline.